Efektivitas UU No. 8 Tahun 1999 Tentang Perlindungan Konsumen Terhadap Perlindungan Hukum Konsumen Sektor Pariwisata - Hotibul Umam; Ilham Pransetyo; Imam Hakiki (Journal Law and Government, 2026)
Consumer protection is an important part of national legal development aimed at realizing the welfare of society and social justice. In the context of tourism, consumer protection is not only concerned with fulfilling the rights of tourists as service users, but also concerns legal certainty for tourism business participants. The study uses a normative juridical approach by examining the provisions of legislation, legal doctrine, and legal norms related to consumer protection in the tourism sector. Consumer protection is seen as part of the implementation of the country’s objectives as mandated in Alinea IV Opening the State Basic Act of the Republic of Indonesia in 1945, namely protecting all Indonesian and all Indonesian blood spills. The rapid development of the tourism sector in Indonesia, which is characterized by the increasing diversity of tourist destinations such as religious, marine, mountainous, and cultural tourism, raises the complexity of legal relations between consumers and tourism business. The Condition demands comprehensive and implementative consumer protection regulation. Tourism consumers in fact cover all walks of life, so protection against tourism consumers is an integral part of protection against Indonesian society. Effective consumer protection is expected to create a sense of security, comfort and legal certainty for consumers while encouraging a healthy and equitable tourism business climate. The results of normative studies show that the legal framework of consumer protection of tourism in Indonesia has been regulated through Law No. 8 of 1999 on Consumer Protection and Law No. 10 of 2009 on Tourism, in particular the provisions of Article 53 which emphasizes the responsibility of tourism business actors. In addition, in the context of Sharia-based tourism, Fatwa DSN-MUI Number 108/DSN-MUI/X/2016 provides normative guidelines on the implementation of tourism that are in accordance with Sharia principles and consumer rights protection.